Gaya Komunikasi Kepemimpinan Situasional Dalam Mengembangkan Kreatifitas Program Acara Di Televisi (Studi Pada GM Production RTV) - Koswara, Nono; Arlena, Wenny Maya; Ahmad, Toni (LUGAS Jurnal Komunikasi, 2023)
Leadership style is how a leader carries out his duties, functions and responsibilities and how the leader is seen and assessed by the employees he leads, or a group that has observed him indirectly. A leader is able to admit his mistakes to correct them, is of service, enthusiasm to continue learning, able to evaluate an event that has been carried out and provide motivation to all employees. Leadership communication in organizations can be illustrated in ways specific in building innovation within the organization. That being said, because a change or new ways are required a specific way too for subordinates, so that subordinates want to work in a new way by new Hope. So it's not just delivering a message, but invites, obeys, to carry out what is desired leader. These specific communication skills in communication organization is called the communication style. The situational leadership theory developed by Paul Harsey and Kenneth H. Blanchard, the emerging leadership style can take four forms, namely: 1. Telling, 2. "Selling", 3. Inviting subordinates to participate, and 4. Delegating. This study uses a qualitative research type, meaning that it uses data that is conveyed verbally and the classification is theoretical. The data taken to test the hypothesis is not processed through mathematical calculations or by various statistical formulas, but the data processing is carried out rationally by way of thinking according to law and logic. The results of research and discussion of how a person leads will depend a lot on the situation at hand at the time it takes place, as well as several other factors that contribute to completing the job, such as the nature of the group of employees or the type of task. Situational leadership theory understands that the needs of organizations are different and that each person has different competencies and commitments. Ideally situational leadership is not only able to consider the type of work or task at hand, but also considers the readiness and emotional maturity of each team member, this needs to be taken into account.